Use of virtual social networks and mental health in times of pandemic - Huamani-Calloapaza, Kelvin Elfer (2022)
Currently, due to pandemic situations due to COVID-19, the use of virtual social networks (RSV) is used very frequently in the adolescent and young population, the need arising through the documented review of analyzing the relationship between RSV and mental health. The objective was to analyze various references regarding the incidence of RSV on mental health. Whose approach was qualitative, using the phenomenological method and the content analysis technique. From the relevant results found, it was evidenced that the use of RSV increased in the COVID-19 pandemic, in academic and social environments, generating a reflection on the need to promote a new approach that contributes to visualizing the opportunities and risks of social networks. RSV. Where the effects of recurrent use affect mental health such as depression, anxiety, irritability, poor academic performance and behavioral disorders.